THE IMPACT OF INFORMATION TECHNOLOGY ON THE EDUCATIONAL PROCESS - Botaeva, G.O. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2023)
The development of digital technologies has had a significant impact on most industries and spheres of life, including education. Currently, the use of information technologies affects the educational process, increasing opportunities in the field of presentation of material, provision of information, organization of the communication process. The purpose of this article is to study the possibility of using information technology in the educational process for its greater effectiveness. Materials and methods. The methodological basis of this article is the literature on the introduction of digital platforms in the educational process, as well as open analytical materials. Results. It is shown that at the present stage of development information technologies have a significant impact on the educational process. With the help of information technologies, the process of providing information for trainees is simplified, communication opportunities in training are increased, as well as the availability of a large number of information resources. With the help of various information tools, it is possible to optimize the process of monitoring the educational process, the analysis of the assimilation of the material by students and their personal achievements. Conclusions. It can be concluded that there are various forms of using information technologies in education, which allow to significantly diversify the learning process. Distance education plays a special role, which makes it more accessible and flexible, which is very important at the present stage. In general, we can confidently predict the further active development of distance education, which is integral to the use of information technology.
Keywords: information technologies; education; distance education; communication tools; digital literacy